THE ANALYSIS OF IDEOLOGIES IN DONALD TRUMP’S POLITICAL SPEECHES ON NATIONAL SECURITY : A CRITICAL DISCOURSE ANALYSIS - Rize Rahmi; Hamzah Hamzah; Fitrawati Fitrawati (Universitas Negeri Padang, 2019)
Although there were many studies of Political Discourse had been done in CDA approach, but still few studies concern withrelation of ideology and language in the discourse. This study aims to, 1) find the ideological discourse structureswhich are used to enhance ideology in political speeches delivered by Donald Trump and 2) reveal the ideologies found in the speeches of Donald Trump about National Security. The analysis in this study is based on Fairclough’s(1992 )framework of Critical Discourse Analysis which consists of three levels of analysis; textual, discursive practice and socio-cultural practice. Then, for textual analysis, the writer used one analytical tool that is the theory of Ideological Discourse Structure of the discourse by Van Dijk (2000). The results showed that Donald Trump used language tactfully to achieve his goal on politics. The conclusion obtained is that Donald Trump enhances fascist ideology in his speeches which can be seen through the ideological structure of discourse which is found in his political speech on National Security.